Jornalismo sensacionalista, mulheres e cidadania: aspectos da presença feminina nas capas do Jornal Daqui - Silva, Lethícia Alves Faria da (2019)
The purpose of this work is to investigate which are the social representations about the female gender in the Jornal Daqui, a popular printed vehicle with the largest circulation in the state of Goias, which also ranks first in the national ranking of largest paid newspappers per year in 2019, according to data released by Instituto Verficiado de Comunicação (IVC). The temporal cut is set on the International Women’s Day, consolidated annually on March 8, as it is a date that expresses all the hystorical fight of women for gender equality. The total sample of the essay is composed by the covers of the mentioned newspaper between the years of 2011 until 2018 and by interviews with semi-estructured scripts with editors, women portrayed and readers of the vehicle. With the undertaking of this analysis, based on a crictical reading of the midia and made effective from the Análise de Discurso Crítica (ADC), we interpellated the newspaper studied to question who the women are and how are they represented in their speech, in order to examine how the vehicle’s jornalistic production incides on the matters refering to the exercise of citizenship of the female gender. The results infer that the Jornal Daqui contribuited to the preservation of gender equality, since congregates women in three aspects: object, vulgarity and body. With that, it is noticed that the represented women are always white, skinny, heterossexual, famous and sexualized, which denotes the maintenence of the status quo by excluding all those that disregard this hegemonic pattern, culminating in the denial of the citizenship to the female gender.